Winter cancellations of elective surgical procedures in the UK: a questionnaire survey of patients on the economic and psychological impact - Baljit Singh; Simon L Parsons; Andrew Wragg; Anisa Kushairi; Philip J J Herrod; Alfred Adiamah; Hannah Boyd-Carson; Prita Daliya; Ahmed M El-Sharkawy; Panchali B Sarmah; Tanvir Hossain; Jennifer Couch; et al. (BMJ Open)
Objectives To quantify the economic and psychological impact of the cancellation of operations due to winter pressures on patients, their families and the economy.Design This questionnaire study was designed with the help of patient groups. Data were collected on the economic and financial burden of cancellations. Emotions were also quantified on a 5-point Likert scale.Setting Five NHS Hospital Trusts in the East Midlands region of England.Participants We identified 796 participants who had their elective operations cancelled between 1 November 2017 and 31 March 2018 and received responses from 339 (43%) participants.Interventions Participants were posted a modified version of a validated quality of life questionnaire with a prepaid return envelope.Main outcome measures The primary outcome measures were the financial and psychological impact of the cancellation of elective surgery on patients and their families.Results Of the 339 respondents, 163 (48%) were aged <65 years, with 111 (68%) being in employment. Sixty-six (19%) participants had their operations cancelled on the day. Only 69 (62%) of working adults were able to return to work during the time scheduled for their operation, with a mean loss of 5 working days (SD 10). Additional working days were lost subsequently by 60 (54%) participants (mean 7 days (SD 10)). Family members of 111 (33%) participants required additional time off work (mean 5 days (SD 7)). Over 30% of participants reported extreme levels of sadness, disappointment, anger, frustration and stress. At least moderate concern about continued symptoms was reported by 234 (70%) participants, and 193 (59%) participants reported at least moderate concern about their deteriorating condition.Conclusions The cancellation of elective surgery during the winter had an adverse impact on patients and the economy, including days of work lost and health-related anxiety. We recommend better planning, and provision of more notice and better support to patients.